ANALISIS KINERJA KEUANGAN PADA PEMERINTAH KABUPATEN TANA TORAJA - Marinus Ronal; Albert Agus Massua (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2022)
Regional Financial Performance Analysis is a form of accountability and a manifestation of financial decentralization and authority from the center to the regions. Regions that are able to manage their finances effectively and efficiently are certainly expected to be able to stimulate the economy through budget absorption in productive sectors and their potential so that they will be able to overall increase efficiency, effectiveness and independence. In this study, the ratio analysis of independence, efficiency and effectiveness is used to see how far the Tana Toraja Regency Government is in managing its regional finances. The results of the ratio calculations carried out resulted in an average independence rate of 22% during the research year (2017-2019). While the results of the calculation of the regional financial efficiency ratio are an average of 88% and the results of the calculation of the effectiveness ratio of regional original income reach an average of 71%.